2013
DOI: 10.1111/jog.12130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estradiol valerate on endometrium thickness during clomiphene citrate‐stimulated ovulation

Abstract: We concluded that the addition of 6 mg/day EV following the CC treatment can prevent the endometrial thinning without perturbing folliculogenesis and ovulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
1
14
1
Order By: Relevance
“…In a study by Satirapod et al, the effects of Estradiol Valerate on the thickness of Clomiphene citrate -stimulated endometrium was examined. They concluded that the administration of Estradiol Valerate following the Clomiphene citrate treatment can prevent the endometrial thinning [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Satirapod et al, the effects of Estradiol Valerate on the thickness of Clomiphene citrate -stimulated endometrium was examined. They concluded that the administration of Estradiol Valerate following the Clomiphene citrate treatment can prevent the endometrial thinning [13].…”
Section: Discussionmentioning
confidence: 99%
“…The use of drugs to improve endometrial thickness is of interest to researchers [11,12]. Endometrial thickness facilitates the embryo replacement, therefore it reduces the risk of spontaneous abortion and also increase pregnancy rate [13]. Physicians have tried to adjust Clomiphene effects using ethinyl estradiol [14].…”
Section: Introductionmentioning
confidence: 99%
“…39,40 Since a thin endometrium is a critical factor for implantation failure, preventing CC induced thinning of the endometrium by adding exogenous estrogens during CC stimulation is important. 8 A relationship between CC treatment and endometrial cancer investigated by many retrospective studies. 41 Ovulation stimulating agents increase serum estradiol levels causing unopposed supraphysiological levels of estrogen during the follicular phase of menstrual cycles of induced ovulation and therefore may also increase uterine cancer risk.…”
Section: Groupsmentioning
confidence: 99%
“…This discrepancy is believed to result from the negative effect of CC on the cervical mucus quality and its antiestrogenic activity on endometrium. [7][8][9] There are several complications of ovulation induction. Functional ovarian cysts have often been observed after ovulation induction.…”
mentioning
confidence: 99%
“…Estrogen therapy is used as one of the effective factors in the treatment of low endometrial thickness without disorder in folliculogenesis and ovulation 18 . Estrogen is received by estrogen receptor alpha (ER-α), and estrogen prevents endometrial tissue atrophy and helps to grow and increase its thickness 19 -22 .…”
Section: Introductionmentioning
confidence: 99%